What really describes the case of Rohingya community in Myanmar? - Ahsan, Abdullahil (Anadolu Agency (AA), 2017)
Although the events have been extensively reported in the international press, what is particularly noteworthy in this Rohingya episode is that most international agencies and institutions find fault with the government in Myanmar.